Treatment outcomes and prognostic factors in oral tongue cancer: a 20-year retrospective study at the National Cancer Center, South Korea - Kim, Min-Gyeong; Choi, Yong-Seok; Youn, Suk Min; Ko, Jae-Hee; Oh, Hyun Jun; Lee, Jong-Ho; Park, Joo-Yong; Choi, Sung-Weon (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2022)
This study aimed to analyze the treatment outcomes and to evaluate the clinicopathological prognostic factors of oral tongue cancer. Patients and.ObjectivesThis study aimed to analyze the treatment outcomes and to evaluate the clinicopathological prognostic factors of oral tongue cancer. Patients and.We retrospectively analyzed treatment results and prognostic factors in 205 patients with oral tongue squamous cell carcinoma who were admitted to the National Cancer Center, South Korea, between January 2001 and December 2020. The patients were treated with surgery and postoperative, definitive radiotherapy (RT) or chemoradiotherapy (CRT).MethodsWe retrospectively analyzed treatment results and prognostic factors in 205 patients with oral tongue squamous cell carcinoma who were admitted to the National Cancer Center, South Korea, between January 2001 and December 2020. The patients were treated with surgery and postoperative, definitive radiotherapy (RT) or chemoradiotherapy (CRT).Eighteen patients (8.8%) were treated with curative RT or CRT, while the rest (91.2%) were treated with surgery with or without postoperative RT or CRT. The median follow-up period was 30 months (range, 0-234 months). The 5-year overall survival (OS) and 5-year disease-free survival (DFS) were 72% and 63%, respectively. Multivariate analysis revealed that a positive neck nodal status (N1, N2-3) was significantly associated with poorer 5-year OS and DFS, while perineural invasion was associated with poorer 5-year DFS.ResultsEighteen patients (8.8%) were treated with curative RT or CRT, while the rest (91.2%) were treated with surgery with or without postoperative RT or CRT. The median follow-up period was 30 months (range, 0-234 months). The 5-year overall survival (OS) and 5-year disease-free survival (DFS) were 72% and 63%, respectively. Multivariate analysis revealed that a positive neck nodal status (N1, N2-3) was significantly associated with poorer 5-year OS and DFS, while perineural invasion was associated with poorer 5-year DFS.Cervical metastasis and perineural invasion are significant prognostic predictors, and combination treatments are necessary for improving OS and DFS in patients with these factors.ConclusionCervical metastasis and perineural invasion are significant prognostic predictors, and combination treatments are necessary for improving OS and DFS in patients with these factors.